2007
DOI: 10.1007/s12039-007-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion binding with dehydroannulenes — Plausible two-dimensional molecular sieves

Abstract: Theoretical investigations have been carried out at B3LYP/6-311++G** level of theory to study the binding interaction of various metal ions, Li + , Na + and K + with dehydroannulene systems. The present study reveals that alkali metal ions bind strongly to dehydroannulenes and the passage through the central cavity is controlled by the size of metal ion and dimension of dehydroannulene cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Theoretical calculations of the structures of graphyne layer fragments and single graphyne layers and their properties were continued in . A number of theoretical works dealt with studying the structures of graphyne crystals consisting of gra phyne layer stacks [39,40], graphyne crystals having a three dimensional rigid cage structure [36,41], and the structure and properties of intercalated and doped graphyne [42][43][44][45][46][47][48][49][50][51][52][53]. Graphyne nanostructures, which are similar to fullerenes, were first theoreti cally studied in [54], and graphyne nanotubes were first described in [55].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations of the structures of graphyne layer fragments and single graphyne layers and their properties were continued in . A number of theoretical works dealt with studying the structures of graphyne crystals consisting of gra phyne layer stacks [39,40], graphyne crystals having a three dimensional rigid cage structure [36,41], and the structure and properties of intercalated and doped graphyne [42][43][44][45][46][47][48][49][50][51][52][53]. Graphyne nanostructures, which are similar to fullerenes, were first theoreti cally studied in [54], and graphyne nanotubes were first described in [55].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the hydrocarbon annulenes and dehydroaryl­[ n ]­annulenes, dehydro­[ m ]­pyrido­[ n ]­annulenes are materials of comparatively recent existence and have consequently been little studied from a theoretical standpoint. ,,, To obtain a deeper understanding of the electronic properties of 1a – d , 2a , b , and 3 , we therefore conducted a DFT investigation on these molecules using the Spartan 08 software at the B3LYP level of theory and employing the 6-31G* basis set. , …”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the hydrocarbon annulenes and dehydroaryl[n]annulenes, dehydro[m]pyrido [n]annulenes are materials of comparatively recent existence and have consequently been little studied from a theoretical standpoint. 75,76,97,98 To obtain a deeper understanding of the electronic properties of 1a−d, 2a,b, and 3, we therefore conducted a DFT investigation on these molecules using the Spartan 08 software 99 at the B3LYP level of theory and employing the 6-31G* basis set. 100,101 Selected frontier molecular orbital (FMO) surfaces (1a,b, 2a, and 3) are shown in Figure 8 along with schematics for clarity, and those of 1c,d and 2b are in Figure 13 of the Supporting Information.…”
Section: Chartmentioning
confidence: 99%
“…6 This also gave a boost to the chemistry of graphdiyne, graphyne and dehydroannulene types of materials. 7,8 The feature which is common to fullerenes, buckybowls, carbon nanotubes, and graphene is that they consist exclusively of sp 2 hybridized carbons, while graphene is supposedly a flat surface, however recent studies has shown that its propensity to distort out of plane is fairly high. 9 Obviously fullerenes, carbon nanomaterials, graphene and buckybowls are exceptional compounds.…”
Section: Introductionmentioning
confidence: 99%